THE SEXIST LANGUAGE USED BY THE CHARACTERS IN THE DUCHESS MOVIE - SANDRA, NARISTA (Language Horizon: Journal of Language Studies, 2013)
Abstrak Seksisme merupakan suatu hal yang memegang peranan penting dalam film ini. Diskriminasi sangat erat kaitannya dengan kemunculan seksisme. Disini para tokoh yang didasari sifat, bahasa dan latar belakang masing-masing yang memerankan peranan penting dalam munculnya seksisme bahasa di alur cerita dalam studi ini. Dalam film yang di produseri oleh Saul Dibb ini, terdapat empat tokoh yang saling berkaitan dengan masalah internal pernikahan antara Duke dan Duchess dari Devonshire yang membuat keberadaan wanita diremehkan dan dipandang sebelah mata. Teori dari Sara Mills digunakan karena berkaitan dengan bahasa seksis baik secara langsung maupun tidak langsung seperti dalam pemilihan kata atau perumpamaan. Terdapat enam tipe bahasa seksis yaitu: kata generik, derivatif, istilah non-paralel yang menunjukkan semantik degenerasi, seksisme dalam pepatah, seksisme dalam kata-kata makian. Melalui hasil tersebut, studi ini mampu menunjukkan efek atau akibat dari keberadaan bahasa seksis dalam film yang berlatar belakang seksisme ini. Kata Kunci: gender, seksisme, bahasa seksis. Abstract Sexism plays an important role in this film. Discrimination is closely associated with the appearance of sexism. The figures here are based on the character personality, language and background of characters which plays an important role in the emergence of sexism in the language of the storyline in this study. The film which was produced by Saul Dibb, there are four interrelated characters with internal marital problem between the Duke and Duchess of Devonshire who makes women presence underrated and underestimated. Sara Mills theory is used because it is associated with sexist language either directly or indirectly as in the choice of words or metaphorical. There are six types of sexist language, namely: the generic, derivative, non-parallel terms that indicate semantic degeneration, sexism in proverb, sexism in swear words. Through these results, this study was able to demonstrate the effect or result of the presence of sexist language in the film which has a sexism background. Keywords: gender, sexism, sexist language. Introduction Socially, women almost differ in terms of social role in the society; they are considered as a person who does not need a high position and education as men had, women are only needed to maintain the housework and caring the children or having a domestic business in order can also keep their babies in the same time. Women always underestimated as the second or lower creature whereas man as the higher than women from any things. This fact will factually create discrimination and gap between men and women. Women is lack of reproductive, sexual harrasment, and men’s violence againts women. In brief, the discourse of women discrimination definitely cannot be separated from the discourse of patriarchal culture. It shows in a lot of part in our country that women mistreatment is still and always exist. Attitudes and behaviour based on traditional assumptions about women, the stereotypes of women, sexual roles in society have been become phenomenon and belief in our life. It comes from every people minds to think and behave through that traditional assumptions. We know that as people no matter the sex wants to treat as well and equal in any aspect of life. Women inhabited a separate, private sphere, one suitable for the so called inherent qualities of femininity: emotion, passivity, submission, dependence, and selflessness, all derived, it was claimed insistently, form women’s sexual and reproductive organization” (Kent, 1990: 30). Allowing the principle that has been made by men assumption and belief, women consciously made by men like dependence, passive, low and tractable. As Susan Kent observes: “Women were so exclusively identified by their sexual functions that nineteenth-century society came to regard them as ‘the Sex’” (Kent, 1990:32). This research studies about some social phenomenon that are found in our society through the visual media such as movie. The aim of this research is to describe the sexist language that used by the characters in The Duchess movie. This research gives understanding of sexist language and the way how it is used in movie dialogue. The kinds of types of sexist language that found in The Duchess movie based on overt sexism and indirect sexism or contextually meaning and the diction based on Sara Mills theory. SEXIST LANGUAGE Researchers are mainly concerned about female and male differences in language use and the reasons behind the phenomenon. They stick to the view that language itself is not sexist, but the society is. The social sexism is transferred to language by human being, and at the same time, sexist and insulting words may reinforce biased view, and changes in the society may be reflected. So language is not only a guide, it is even a mirror that reflects the sexism in social reality, and at the same time, it makes people see the social reality more clearly. Sexist language is language that expresses bias in favor of one sex and thus treats the other sex in a discriminatory manner. In most cases, the bias is in favor of men and against women. All kinds of unequal phenomena in society including gender bias are bound to be reflected on its lexis. Gu Jiazu (2002) thinks English as a sexist language is marked with distinctive sexist factors, among which the lexis is the most important aspect. There also have been many critical feminist surveys of English lexis (Nilsen et al., 1977; Schulz, 1990) which have argued that sexism is inherent in many of the labels which English speakers use. Some feminists have pursued the idea that there exist lexical gaps in the language-aspects of women’s lives which are commonplace, but have no words to describe them (Spender, 1985). So it is frequently argued that these usages are sexist. Mills suggests that there are two forms of sexism which are overt and indirect sexism. Overt sexism is clear and unambiguous, while indirect sexism can only be understood contextually in relation to the interpretation of surrounding utterances. Indirect sexism is extremely common and therefore need ways to challenge and analyze its usage in language. (Mills, 2008). OVERT SEXISM According the Sara Mills’s theory, there are two types of sexism which are overt sexism and indirect sexism. Overt sexism is one of the parts of sexism which can be clearly be understood with some forms that can be generalized about linguistically and contextually. Overt or direct sexism is the type of usage which can be straightforwardly identified through the use of linguistics markers, or through the analysis of presupposition, which has historically been associated with the expression of discriminatory opinions about women, which signals to hearers that women are seen as an inferior group in relation to males. (Mills, 2008:11). There are some forms of overt sexism such as: Generic nouns, derivational, non-parallel term, sexism in proverb and sexism in swear words. In the other hand, there is also indirect sexism. It necessary to consider more details the proposition. It will be rather difficult to analyze because the reader can be understood because the reader must be really understand with the transparent source of data as like in the script. It shows indirectly in metaphor and irony that usually exaggerate in stereotyping one sex. In society, men are considered the norm of the human species. They are viewed as those representing all the human beings, male and female. Simply, it can be said that “male = “human” norm. This practice makes women invisible in language. In addition, it marginalizes women and reflects a male dominated society. In accordance to that, Sara Mills and some supporting linguists gives a guideline how to identify the linguistic structure differences used in English, we can analyze morphologically by these following ways: a. Generic nouns Another well-known example of generic masculine term is “man”. Man and woman as two equal components of human race are actually not equal in English lexicon. Man, besides its reference to male human being can also refer to the whole race. The usage in a general sense of man makes woman invisible. For example; (1) All men must die. (2) Man is a social animal. It is easy to see that “man”, and “men” can be used generically to refer to both male and female. In the first sentence the word Men refers to human being. Despite this, in the second sentence also state the word Man in which it is a human species or animal. Thus, man makes males linguistically visible and females linguistically invisible. From this, one can know that in English using “man” or “men” indicates “the human race”, they treat man as the center of the society, an embodiment of criterion and totally ignore the existence of woman. b. Generic Pronouns (he, his, him) In English there are a group of nouns of common gender, which refer to either male or female such as student, person, teacher, etc. When such nouns are used with generic reference in single form, the traditional grammar advocates to use the masculine pronouns in the context for the purpose of coherence with generic nouns.( Zhang Zhenbang,1995). Generic pronouns are pronouns that are said to refer, with equal likelihood, to woman and men. But the English language ignores women by allowing masculine terms to be used specifically to refer to males and commonly to refer to human beings in general. According to the rule of traditional grammar when the indefinite pronoun one is used for generic reference, then in the context usually one, one’s, or himself is used to be its relevance. But in order to avoid repetition, he, his, him, or himself is chosen, especially in American English (Zhang Zhenbang,1995) See the examples: (1) If one wants to see the ruins, he must find his own guide. (2) Everyone must do his work well. In the first and second sentences, one and Everyone refers to the concept of people, which is a concept of common gender, we do not know they are men or women but it uses masculine pronoun. He and his in the context formally manifests the imagery of men but semantically represents people of either gender. The operation of the grammatical rule conventionally elevates the status of the masculine pronouns and lowers the feminine ones. c. Derivational “In English, derivational morphemes are mainly prefixes and suffixes. These affixes often change the part of the stem. The affixes thereby help us to identify relationships within words”. Derivation is a way of word formation. It forms a word with meaning and category distinct from that of its base through the addition of an affix. The original base is the core of the formed word and carries the main complements of its meaning. The affixes are always bound morphemes, which carries information about meaning or function. In English lexicon, one of the most obvious evidences of the sexism is the affixes which lead to a view of women as a derivation from a male term. The feminine one is always derivative of the masculine one by adding a feminine suffix such as -ess and –ette. Actor, for instance, with the meaning of “a person who plays the part of a character in a movie or play”, when attached to a feminine suffix –ess, becomes actress with the meaning of “woman with profession similar to those of “actor” and as for –ette, when usher is adhered to –ette, it becomes usherette. Such pairs of the words are of long lists in English lexicon. Here just list some of sexist based on its derivational: Ambassador - ambassadress Prince - princess Poet - poetess Author – authoress Waiter – Waitress Manager – Manageress That some of lists of sexist derivational word have different meaning based on the classification usage for men or women. The examples show and prove that the suffixes -ette and –ess are for woman only. It is considered sexist because when men do not need any affixes to refer to them, women need it. Furthermore, the terms in the right side are the feminine terms which are only indicated to the women only. Those feminine accents in the words ambassadress, duchess, princess and poetess and so on are not referred to the men or even to all human being, but those are especially marked to the women. d. The Non-Parallel Term The non parallel term between men and women are also the real example how sexist the English is. In accordance to that, Lakoff pointed out that words that were once equivalent terms for males and females have often diverged in meaning over time. (Chaika, Elaine.1982:205). Non parallel term or semantic derogation between men and women are also the real example how sexist the English is. In accordance to that, Lakoff pointed out that words that were once equivalent terms for males and females have often diverged in meaning over time. Consider these following examples: Mrs, Ms – Mr Mister – Mistress Governor – Governess Lady –Lord Lady – gentleman From the description above, none of feminine terms in the list connotes the same degrees as the masculine terms and almost all of them acquired as secondary sexual connotation. Lexicographers have noted that, once a word or term becomes associated with women, it often acquires semantics characteristics that are congruent with social stereotypes and evaluations of women as a group, a process that has variously been termed ‘semantic derogation’ (Shulz, 1975), ‘semantic degeneration’ (Miller and Swift, 1976) and ‘semantic polarization’ (Eakins and Eakins, 1978). e. SEXISM IN PROVERBS Proverbs are a short pithy saying in common and recognized use; a concise sentence, often metaphorical or alliterative in form which is held to express some truth as-curtained by experience or observation. The fact that there are many English proverbs which contain the words discriminating, distinguishing women, making women are worry about it. Since proverbs are standard, it is hard to change and create new proverbs substituting the old ones. Consider these following examples of English proverbs: 1.“A man is as old as he feels, and a woman as old as she looks” this example implicitly creates an image that this sexist saying suggest that men age better than women. 2. “A man’s home is his castle”. This example also discriminate the women. It implicitly create an image that the peaceful and lovely house is only man has. 3.“A good man is hard to find” the proverbs means that the difficulties for woman to fin a good man that is suitable for them. Or in finding male patner. f. SEXISM IN SWEAR WORDS The swear words is an expression in sometimes conscious or unconsciously said by speaker who is in a bad condition. In some area swear words is a kind of taboo to say, but in the others are very common and probably become a habit. Those swear words are used to insult, to curse, to offend, or to mock at something or someone when the speaker strong emotion which the impact can trivialize women position. Swearing is the way someone uses obscene words orally to insult, to curse or even to offend something (someone or action). Also, for emphasizing when the persons have strong emotion (Hughes, 1991). Usually, when someone has been insulted, someone will feel offended and easy to be angry. According to Crystal (1997) as cited in (Adeoye: 2005), sexist swear words is regarded as an emotive or expressive function of language. Hughes (1991: 224-225) claims that people tend to swear when he/ she angry or disappointed. They are also likely to swear when they would like to express antagonism, frustration, surprise, anger, and shock. Usually some words that belong to this category are fuck, cunt, shit. Swear words are very common in people’s ears, because it sometimes said in the public society or even in the movie. There are several reasons why does swearing occur: 1. To express feeling in words rather than in actions, especially if you do not have bigger vocabulary (Crystal, 1995: 156). 2. To express their anger and frustration. 3. To seem brave. 4. To make people afraid when they have been violence by someone in the form of sex or other violence. 5. To imitate what other people do. There are very little swear words have been written for language learners, yet nearly all- native speakers use it in daily communication. The term such as: “fuck”, “damn”,”bastard”, “son of a bitch, “motherfucker”, “asshole”, and “bitch”. That can be used as the examples of sexist swear words which provoke the violent confrontation. In other words, according to Eisenson and Boase (in Liedlich, 1973: 107), there is some words that is not supposed to be say in the public society, because it brings the negative meaning for the speaker also the listeners. It also makes a bad habit that the speaker feels very common. If there is someone uses obscene words to swear other people will judge them as people who are impolite, do not have high and well education or having less vocabulary. Those examples above are definitely can refer to both sexes man and women. Unfortunately, in practice those words are mostly indicated to the women behaviors and attitudes. It is the fact that English has linguistic and semantic discrimination through the practice of language usage; it is briefly can be seen in the word motherfucker and bitch. INDIRECT SEXISM According to Sara Mills, she said that indirect sexism is ironising sexism. Since it both challenging overt sexism and keeps it in play. Benwell (2006) terms this type of indirect sexism ‘new sexism’. She also adds that it’s very reminiscent of, it is not identical to past forms of sexism which clearly shown. It differentiates of they way overt sexism and indirect sexism is used. This type of new sexism is bring the outdated notions of sexism become new term one. That is why Williamson also called this new type of sexism as ‘retro-sexism’. The fact that the humor and irony are used when being sexist does not change the nature of sexism itself, but it just only interpreting simply and different way of respond the new sexism. This term of sexism used to categorize a set of stereotypical beliefs about women which cannot be directly related to a certain linguistic usage or features. (Mills, 2008:10). Overt sexism is now largely seen as anachronistic and so it has been driven underground; indirect sexism is one which in some ways attempts to deny responsibility for an utterance, mediating the utterance through irony or disguising the force of the sexism of the utterance through humor, innuendo, embedding sexism at the level of presupposition, or prefacing sexist statements with disclaimers or hesitation (Mills, 1998:135). Indirect sexism can be found in several aspects such as humor and irony, scripts and metaphor. For example in jokes, it is a complex way constituting women as ‘minority group’ without taking responsibility for that exclusion. Sexist jokes allow generally unacceptable views of women to be expressed, because the person usually tells the jokes generally can claim that they themselves did not make up the joke. (Mills, 2008:71). Metaphor The narrative pathway or script is brought to play in new reports about women and men in a public sphere. This indirect sexism refers to women implicitly. It uses things to refers to the object either men or women. Irony Irony is a common strategy for humorous remarks about women. The term of ironic sexism is often satire the object in polite way. Irony involves a difference or contrast between appearance and reality - that is a discrepancy between what appears to be true and what really is true. RESEARCH METHOD According to Bogdan and Taylor in Moleong (2007:4), descriptive qualitative research is a research procedure that represents data either written or spoken from the people and behaviors which can be observed. In addition, Krik and Miller in Moloeng (2007:4) defines the descriptive qualitative ad a certain tradition in social sciences fundamentally relies on human observation in its own religion and deals with these people in language and terminologies. Qualitative research is mostly associated with words, language and experiences rather than measurements, statistics and numeral figures. Furthermore, in analyzing the types of sexism which are used by the characters of The Duchess Movie, it will be conducted by using the descriptive qualitative research. Qualitative approach is taken because the decided research efforts in discussing, analyzing and finding the social phenomena which is running naturally; it is not a controlled or based on laboratory research. The collected data are the subjects of experiences and perspectives; the researcher attempts to arrive at a rich description of the people, objects, events or conversations and so on. The data are from the words, phrases, clauses, or sentences that found in the dialogues of some characters. The researcher uses this method because she wants to get a brief description and a rich understanding about the expressions of sexist language and the classification which categorized as sexist gender biased based on linguistics terms in The Duchess movie. The source of the data which is used by the researcher is taken from the conversation or dialogues which is in the script and the movie of The Duchess. The characters who will be analyzed are Georgiana as a Duchess, The Duke Devonshire, Lady Elizabeth (Bess), and Charles Grey. In addition, to avoid the research becomes wide and broad, the researcher used a theory to identify and to classify, identify and analyze the types of sexist language. There are some theory which is gathered some sexist theory to support and complete the main theory. This study used the theory of Sara Mills in “Language and Sexism” and Philip M. Smith “Language, The Sexes and Society”. It also helpes and completes by some supporting theory from other linguists in describing the types of sexist language in journals. The reason of the researcher gathers and combines the theory because to make the analysis become details and complete. It also adds some information of sexist language types. Most of the data will be found in the types of overt and indirect sexism, because the researcher concern in the words, phrases, utterances or sentences in many setting in this movie. The researcher chooses those characters because the other characters do not influence much about the gender discrimination which appears in the story. The theme of this movie is about internal gender discrimination in The Duke and The Duchess marriage, so it is not possible for other characters to interfere. In the technique of the data analysis, the researcher begins to analyze the data toward the procedures. In conducting the research procedure, the researcher follows three steps. The first, the researcher classifies the data which are words, utterances or sentences in based on its types of sexism orderly. The second, the researcher describes those data based on the two classifications of sexism which are overt and indirect sexism. The data is in the form of words, proverbs and utterances. The third, the researcher describes the existence of the sexist language which exists in The Duchess movie. DISCUSSION The analysis of sexist language or expression in discriminating sexes inappropriately above is used to drawing attention to the way language used to represent women in that movie. According to the data analysis and finding of the types of sexist language linguistically above, the researcher found six types of sexist language in The Duchess movie. They are consist of sexism in word such as the use of generic noun, derivational, non-parallel term which shows semantics degeneration, sexism in proverbs, sexism in swear words, and indirect sexism such as metaphor and irony. Some characters such as The Duke (William Cavendish), Duchess (Georgiana Spencer), The Duke’s mistress (Lady Elizabeth Foster) and Georgiana’s secret affair (Charles Grey) are used some term in sexist language by Sara Mills in the movie. The generic noun is term which is used to refer both men and women, but in effect it often refers to men only. Generic noun perform very useful function of allowing us to refer to an entire class of entities with a single word, and most if not all languages have one or more forms that can be used to designate members of the human species in general. This term applied when the speaker Georgiana unconsciously says in her speech when The Duke and her held in Bath Assembly room at night. She said that, “only two specimens of this rare bird are known to man.” The word man here is used to gather both men and women knowledge about the two rare bird. She uses that word because of the reason for the recent attention surrounding this term is the growth of awareness about the portrait of the social order implied in which the male are half of the species whose members dominate. The word “man” used by Georgiana is because to respect the dominating of male in the society. People often refer to themselves and using nouns that describe an occupation or performance of an activity, such as “Duchess” in the datum (2), “Let them talk! Grey makes me a fallen woman, well and good, now William may divorce me and Bess becomes Duchess of Devonshire!”. It seems clear that the great majority of such terms more readily evoke the image of man than of a woman. Some feminists have argued that the addition of diminutive suffix to agent nouns results in the term that have less semantic potency than unaltered counterpart, and that this both causes and reflects a devaluation of those who occupy this agent roles (Smith, 1953:46). Derivational suffix which found in this movie takes when Georgiana or the speaker says emotionally that Bess can become a Duchess of Devonshire in The Duke allows and gives his arrangement to have a relationship with Charles Grey. Based on the definition of the word “Duchess”, it means as a noblewoman or a woman holding a rank equivalent to duke in her own right. Duchess (female) can either be a monarch ruling over a duchy or a member of the nobility, historically of highest rank below the monarch. The word “duchess” is added by feminine suffix –ess to identify that the agent noun uses female reference. Based on the representation of Duke and “Duchess”, they are different. Duke tends to manage the social economy, politic, and something which is valuable. In inversely different with the job description of “duchess” who is only manage about the simple thing. In addition, the position of “duchess” in this movie shows that also, she has no special except in little space in Whig, and for the rest she only cares about what she should care as a mother. Based on the job description of “duchess”, it shows that the position of The Duke always becomes superior. So, when there are agents nouns placed in one sentences, it seems that the old maxim “Duke and Duchess” is more honored in the breach than the observance. In fact, little is known about the psychological significance of the word order pairs like this, and the fact that women often come second or may not signify to the listener that they have less status or importance than the male. In addition, the term of non-parallel implied because of some reason deals with women social status at that time. “Mr”, “Mistress”, “Lady/ladies - Gentlemen”, “Governor”, and “Lover” are the sexist language which found in the movie. From those words, we can see that there is no similar meaning from its pairs. Meanwhile, those words have implicit meaning which degenerates women become lower status from the pairs. It can be conclude that most women as the speaker of the words above are aware about the condition of women whom trivialized by men physically and mentally. From the word “mistress”, “lady” and “lover”, all of them have similar meaning as women who are become a man maid of desire or tend to be having lower status. While the word “Mr”, “governor” and “gentlemen” are also treated as sexist because it has higher social status than its pairs. None of feminine terms in the list of data above connotes the same degree of strength or power as its masculine counterpart, and almost all of them have acquired as secondary sexual connotation. The character of The Duke in the datum (8), “That’s one way of putting it. Your mother called it ‘common decency before personal gratification’, or some such thing… the exact words escape me…” shows about the sexism in proverb about the matter of social interest. He tries to give an example from Georgiana’s mother quotation which grabs by him. According to the definition of proverb, it means short pithy saying in frequent and widespread use that expresses a basic truth or practical precept. In general use, that proverb states about a general truth or piece of advice to the hearer, Georgiana. That proverb has an implicit meaning that the position of the Duke is always strong in the matter of conducting his wife. In the other words, Georgiana has to follow what her husband as to do. In this circumstance, the position of Georgiana is awry. She has to choose between her children or her desire and affection of Charles Grey which she doesn’t get from her husband. As the main Character, The Duke always becomes the centre of the society. He should speak politely. In the other hand, in some cases he cannot put himself in that situation. Based on The Duke character personality, he kinds of man who is introvert, cannot control his emotion and has a switch temper that can be changed in certain time. So, he often expresses his anger or dissatisfaction through something near him. He also often use sexist swear word to release it such as “damn”, “hell”, and “bastard”. Those words are deal with death term which uses to mock or curse people. That term also to express The Duke feeling rather than in action, especially he does not have bigger vocabulary. In the datum (15), “Give me a son and then do what the hell you want, as long as you do it discreetly. Until then you stay here and do as I say.” The Duke says “hell” to express his frustration of his failure to obtain a male heir from Georgiana. Furthermore, this sexist swears word helps by his action in intimidates his wife by hurting her in action. The other main characters, Georgiana often use parable or imagery to reflect her own circumstances. The imagery and parable itself categorized as indirect sexism term. The data which treated as indirect in the movie are “male company, “imprisoned”, “throw”, “you both of another world that does not exist and never will” and “love is an act! It’s more than words and undying oaths!” That indirect sexism consists of metaphor and irony. As the definition of indirect sexism, it cannot be understood by linguistics markers but using contextual meaning. Metaphor is a figure of speech in which a word or phrase is applied to an object or action to which it is not literally applicable. It can also regards as representative or symbolic of something else, esp. something abstract. In this case, the character of Georgiana often uses this term to symbolize herself which is bridled in her own internal marriage problem. The other character, Bess also express her sadness and disappointment of being left by her husband because of his “mistress” in datum (5). The fact that metaphor and irony are used when being sexist does not change the nature of sexism itself, but it rather simply changes the way it can be responded to. From those terms of sexist languages which found in The Duchess movie, it can be concluded that the sexist language related with those character because of the impact of the sexist theme occurs in that internal marriage problem. The impact of those sexist languages to the theme of the movie is when those utterances make the women participation underestimated more. The significance effects shows when inequality between men and women, social inequalities which women have and the position of men who do not want to be defeated by circumstances of women influence to the theme of the movie. The existence of sexist language is also because the aspects of character personality, language, background and its context. Character personality takes part in the analysis because the speakers unconsciously speak it refers to their character. For example like The Duke, he often uses kind of sexist swear word in order to replace his anger in to the word or someone close. It is because The Duke is introvert, close and has a switch temper which can be changed in certain time. It similar with Charles Grey, as a man, he also temperamental when he knows something inappropriate as like Georgiana fake promise and prefer to go back for her children rather than him. In the other hand, if Georgiana and Bess as representative from women sides they tend to be polite and use their feeling rather than logic in their problem. The choice of word which used by those characters mostly reflects their circumstances as women at that time. From those characters personality, we can see that words which that use reflect each people characters. That choice of words absolutely influences to their language when they speak such as in the term of sexist swear word which mostly expressed by The Duke. Furthermore, character personality and language cannot be separated with the context and background of each people and movie at that time. The speakers will consider the language which they will use based on the context of the talks. The background here used to support the situation of the character based on place and time in their situation or in this case is in Victorian era. The background may be a stereotype or culture of certain gender. The most data commonly found in non-parallel term, indirect sexism and sexism in swear words. It is because the women condition cannot be equated with men. People at that time still holding patriarchal culture which means the position of men is superior and holding every aspect. They often underestimate women self-esteem to become men mistress whom can be throwing away anytime. Women seem like do not have strength to be independent without men position in front of them. Men are allowed to have more than one mistress even they are a centre of society. On the other hand, when women try to express their feeling to other men it considers as improper behavior and taboo. All of utterances which have been said by the characters are reflecting their character personality. Based on the explanation of the existing of sexist language above, there are some reasons that make the women circumstances become weak in physically and mentally. This evolutionary reasoning provided justification for the emotional and mental differences between men and women. At last, sexism can be existing because of stereotype of women and it reflects to the culture. The character personality helps to make it clear where the mental and emotional aspects involve in indicating their existence through language. Those stereotypes create morals and social values that applied until this time. The only way of changing that social structure is to make the position of men and women equally same no matter what. CONCLUSION This chapter presents the conclusion and suggestion based on the analysis and finding in chapter four. The finding shows the sexism by the characters in the movie involves overt and indirect sexism. Overt sexism is a type of usage which can be identified directly through the linguistic markers. While indirect sexism can only be understood contextually in relation to the interpretation of surrounding utterances. However, this term of sexism used to categorize a set of stereotypical beliefs about women which cannot directly analyzed by linguistic features. The linguistics features of sexism are divided into several types, as follows: (1) Sexism in words. The using of man in “Well, only two specimens of this rare bird are known to man” considers as generic nouns which should be referred to both of sex. (2) Sexism in words of using English pairs or word order of words showing non parallel term or semantic degeneration between men and women such as the word Mr “In the play this evening, there was a scene in which Lady Teazle and Mr. Surface discuss their affair”, Ladies, gentlemen, and mistress “My husband, Mr. Foster, is enjoying his mistress in Bournemouth, and I wanted some diversion.”. This non parallel term shows that there are semantic derogations between men and women position. (3) Sexism in words using suffix –ess in “Let them talk! Grey makes me a fallen woman, well and good, now William may divorce me and Bess becomes Duchess of Devonshire!” as job occupations of profession such as Duchess. This type of sexism in words shown that the discrimination through gender divisions still exists in the matter of word order. (4) Sexism in Proverb. There is only one analysis which found as sexism in proverb as like “common decency before personal gratification”. It related to the high power of men than women. This kind of English proverb seems like the metaphorical of men who held to express the position of men that is always unbalance and prioritized than women. (5) Indirect sexism. This new term is not related to the certain set of linguistic usage and features but contextually of a diction which replace and describe their speaker situation. Indirect sexism which found in this research is about metaphor and irony such as “How about ‘imprisoned’ in my own house’?” and “I’m ill at ease with male company for the moment.”. (6) The last is sexism in swear words. There are various kinds of swear words which used by the character of the movie such as “hell” as like this utterance: “Give me a son and then do what the hell you want, as long as you do it discreetly.”, “bastard” in this utterance:“Three boys??? Do you think I can make those bastards my heirs? Well, do you?” and the insulting term for women such as “whore”, “Be quite you fool! (to Georgiana). Are you his whore?!”. The usage of sexist swear words express their disagreement, anger or objectionable depends on the context and problem of the character. In addition, there is no general neutral term to replace the words. The last is In addition, some aspects of sexist language existing in the movie are character personality, language, background and its context. All of those aspects are interrelated and interconnected each other. Based on the finding, the character personality influences more because it reflects to their language they use. Their language will refer to their position as a centre role model that perceived by public. While the background and context reflects women stereotypical knowledge in Victorian era which bring the character of women discriminated by men. SUGGESTION Using a language without regard to the gender classification is expected to minimize the woman discrimination in the language. So, the researcher wants to contribute some suggestion for the next researcher. First, the next researcher can use and complete the analysis by new sexism which is indirect sexism. It used to analyze sexism without directly using linguistics markers but, it uses diction like in metaphorical, humors, irony or satire which trivializes women. Second, the researcher hopes that the next researcher analyzes the source of data by putting the historical background so that they can find out the characteristic of their style of writing. The historical background can use to prove why those sexist languages occurred. Lastly, the researcher hopes that the terms of English indirect sexism will be applied to avoid the use of sexism in written and spoken even it is not linguistically shown in the next research. DAFTAR PUSTAKA Aini, Nur, 2010. The Sexist Swear Words Used by the Characters in Shottas Movie, English Letters and Language Department, Faculty of Humanities and Culture, Maulana Malik Ibrahim State Islamic University of Malang. Brannon, Linda. (2002). Gender: Psychological Perspectives. Chapter 7: Gender Stereotypes: Masculinity and Femininity (pp. 152-76). London: Allyn and Bacon. Cameron, Deborah. (1985). Feminism and Linguistic Theory. London: Macmilan Press Chaika, Elaine. 1982. Language the Social Mirror. Massachusetts: Newbury House Publishers, Inc. He, Guimei. 2010. Journal of Language Teaching and Research of An Analysis of Sexism in English. Academy Publisher manufactured in Finland: Qingdao University of Science and Technology, Qingdao 266061, China. Vol. 1, No. 3, pp. 332-335, May 2010. Holmes, Janet. 1992. An Introduction to Sociolinguistics. Addison Westley Longman, Inc., New York. Johnson, Allan G. 2000. The Blackwell dictionary of sociology: A user's guide to sociological language. ISBN 978-0-631-21681-0. Retrieved November 21, 2011. Kent, Susan. 1990. Sex and Suffrage in Britain 1860-1914. Princeton: Princeton University Press. Lei, Xiaolan. (2006). Sexism in Language. Northwest Polytechnic University, China. Vol. 5, No.1. Lewin, Miriam (Ed.), In the shadow of the past: Psychology portrays the sexes. New York: Columbia University Press. Lexy J. Moleong, 2007. Metodologi Penelitian Kualitatif, Bandung: PT. Remaja Rosda Karya. Linda Sofia, 2008. The Sexist Language of Jokes Column in Hello Magazine. Thesis, English Letters and Language Department, Faculty of Humanities and Culture, The State Islamic University of Malang. Mills, Sara. 2008. Language and Sexism. Cambridge University Press, New York. Parks, J. B. & Roberton, M. A. (1998). Contemporary arguments against nonsexist language: Blaubergs (1980) revisited. Sex Roles, 39(5&6), 445-461. Smith, Philip M. 1953. Language, Sexes and Society. Basil Blackwell Inc, New York. Wardaugh, Ronald. 1986. An Introduction to Sociolinguistics. Oxford: Page Bros. INTERNET SOURCE http://www.encyclopedia.com/topic/Sexism.aspx (accessed in January 10th 2013) (http://en.wikipedia.org/wiki/Sexism). (accessed in January 10th 2013) http://digilander.libero.it/mgtund/sexism_in_language%202.htm (accessed in March 1st 2013) http://www.victorianweb.org/gender/sextheory.html (accessed in March 28th 2013) http://webpage.pace.edu/nreagin/tempmotherhood/fall2003/3/HisPage.html (accessed in March 28th 2013)